Attitudes towards service robots in domestic environments: The role of personality characteristics, individual interests, and demographic variables - Reich Natalia; Eyssel Friederike (Paladyn, 2013)
The majority of EU citizens report a positive view about robots in general according to recent EU-level survey data. However, does this also hold true for attitudes towards service robots in particular? To investigate this research question, we conducted a survey on a representative sample from Germany. Importantly, we explored the role of demographic variables, interest in science and technology, and personality traits associated with psychological anthropomorphism in determining perceived acceptance of service robots in everyday life. Overall, attitudes towards service robots turned out to be relatively positive. Moreover, demographic variables (e.g., gender, occupation), interest in science and technology, and dispositional correlates of anthropomorphism had a significant impact on attitudes towards such assistive technology.